Effects of solid fat content in fat particles on their adsorption at the air–water interface. (October 2018) - Hanazawa, Tomohito; Sakurai, Yoko; Matsumiya, Kentaro; Mutoh, Taka-aki; Matsumura, Yasuki
Abstract: The role of solid fat content (SFC) within fat particles was examined for its effects on adsorption behaviour at the air–water interface. Three kinds of vegetable oil with different SFC profiles were mixed with a sodium caseinate solution (2% w/w) to prepare the creams, whose fat contents were adjusted in the range of 0–40% w/w. The decrease of interfacial tension at the air–water interface was measured for creams and the sodium caseinate solution, and the ratio of the maximum decrease rate of creams (Δγmax )-to-the sodium caseinate solution (Δγ0max ), Δγmax /Δγ0max, was calculated. The interfacial elastic modulus (E′) of creams and sodium caseinate solution was also measured and found to initially increase with time but decreased after the maximum value (E'max ). Both Δγmax /Δγ0max and E'max were affected by the temperature, fat content of creams and SFC in fat particles. The largest increase for Δγmax /Δγ0max and E′max was observed when the SFC of creams was between 10 and 50% w/w. The microscopic structures of the air–water interface of creams after whipping were also affected by the SFC, such that fat particles containing 28.4% SFC were found to adsorb and aggregate at the air–water interface layer. These results suggest that the adsorption of fat particles onto the air–water interface and interfacial structure formation by adsorbed fat particles were promoted via partial coalescence. Graphical abstract: Image 1 Highlights: Three kinds of cream with different solid fat content (SFC) profiles were prepared. Interfacial rheology of the air–water interface in the creams was measured. Results were affected by temperature, fat content and SFC of the creams. It is suggested that partial coalescence promotes fat particle adsorption. It is also suggested that partial coalescence strengthens the interfacial structure.